2014
DOI: 10.1371/journal.pone.0105822
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical and Bacteriological Factors for Optimal Levofloxacin-Containing Triple Therapy in Second-Line Helicobacter pylori Eradication

Abstract: Quinolone has the disadvantage of easily acquired drug resistance. It is important to prescribe it wisely for a high eradication rate. The current study aimed to determine the clinical and bacteriological factors for optimal levofloxacin-containing triple therapies in second-line H. pylori eradication. We enrolled a total of 158 H. pylori-infected patients who failed H. pylori eradication using the 7-day standard triple therapy (proton-pump inhibitor [PPI] twice daily, 500 mg clarithromycin twice daily, and 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 39 publications
0
31
2
Order By: Relevance
“…Studies reporting duplicate data were excluded. After careful evaluation, 36 studies (including 3466 patients) were found to perform antibiotic susceptibility determinations and were included in the systematic review. Of these 36 articles, 24 reported cure rates according to antibiotic resistances/susceptibilities, including 37 arms of treatment.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies reporting duplicate data were excluded. After careful evaluation, 36 studies (including 3466 patients) were found to perform antibiotic susceptibility determinations and were included in the systematic review. Of these 36 articles, 24 reported cure rates according to antibiotic resistances/susceptibilities, including 37 arms of treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Nine additional articles performed endoscopy in all patients but did not state whether the procedure was an inclusion criteria or whether patients who rejected endoscopy had been excluded . In another 10 articles, endoscopy was not performed in all patients but the reasons for not doing so were not stated, nor whether endoscopy was offered to all patients . In this group, endoscopy was performed in 682 of the 1189 patients included (57.4%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, 61 arms (30%) showed PP cure rates >90% . Two studies (two arms) evaluated a dual therapy (rabeprazole and amoxicillin), 34 arms evaluated a triple therapy (Table ), and 25 arms evaluated quadruple therapies (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Worth noting is that such a therapy achieved an encouragingly high (87.5%) eradication rate. A similarly prolonged levofloxacin-based triple, with double-dose PPI, achieved 84.8-93.6% success rates in Taiwan [24,25]. However, when a regimen with increased doses was administered for only 8 days, the eradication rate was only 60-64% [26].…”
Section: Discussionmentioning
confidence: 99%